Identification of the Nosema spp., a microsporidian parasite isolated from the honey bees (Apis mellifera) and its association with honey bee colony losses in apiaries of Iran - Moeini, Sahar; Malekifard, Farnaz; Tavassoli, Mousa (Journal of the Hellenic Veterinary Medical Society, 2022)
The aim of this study was to determine the Nosema species by microscopic and molecular method and its association with honeybee colony losses (Colony Collapse Disorder) in apiaries of Urmia, Northwest of Iran. For this purpose, honeybee samples were collected from 840 colonies kept in 120 apiaries in five different location of Urmia. The specimens were examined for the presence of Nosema spores. After DNA isolation, the 16S rRNA gene was evaluated using multiplex PCR. Total infection prevalence with the microscopic evaluation was 32% while in PCR test was 58.2%. Nosema positive samples were evaluated by PCR sequencing. Based on the results of PCR, all identified cases were N. ceranae. The obtained sequences were transferred to GenBank/NCBI (samples accession numbers MT001887 and MT001893). The results showed the prevalence of Colony Collapse Disorder like symptoms in the studied honeybee colonies were 13.33%. N. ceranae was detected by PCR in 20.28 % of honeybee colonies with Colony Collapse Disorder like signs. Our findings showed that there was a significant relation between Colony Collapse Disorder and presence of N. ceranae. The results of this study concluded that N. ceranae is the only specie that affects the honeybees which may have an important role in the occurrence of collapse of bee families and depopulation of hives in this area.